2014
DOI: 10.1002/bio.2620
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent solid phase for sialic acid determination: a promising sensor for milk‐adulterated samples

Abstract: This article presents the synthesis, characterization and spectroscopic study of silica modified with thenoyltrifluoroacetonate (SilTTA) and coordinated to an europium (III) ion, for the determination of sialic acid (NANA). Elemental analysis and infrared spectroscopy suggest silica functionalization, as well as coordination of beta-diketone to the lanthanide ion. The emission spectra of compound-free and coordinated Eu-SilTTA to NANA showed significant changes with respect to the maximum emission and spectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…385 Alves et al reported a solid-phase fluorometric assay of Nue5Ac with LDR and LOD 0.4-2000.0 and 0.4 mg L −1 , respectively, by incubating Nue5Ac with EuIJIII)-coordinated silica modified by sodium thenoyltrifluoroacetonate in ethanol (carbonate buffer pH 6) for 3 min and measuring the fluorescence intensity at 615 nm for a photoexcitation at 345 nm. 386 Several photoluminescence assays based on phenylboronic acid linked established fluorophores viz. CdTe, fluorescein isothiocyanate, etc.…”
Section: Photoluminescencementioning
confidence: 99%
See 1 more Smart Citation
“…385 Alves et al reported a solid-phase fluorometric assay of Nue5Ac with LDR and LOD 0.4-2000.0 and 0.4 mg L −1 , respectively, by incubating Nue5Ac with EuIJIII)-coordinated silica modified by sodium thenoyltrifluoroacetonate in ethanol (carbonate buffer pH 6) for 3 min and measuring the fluorescence intensity at 615 nm for a photoexcitation at 345 nm. 386 Several photoluminescence assays based on phenylboronic acid linked established fluorophores viz. CdTe, fluorescein isothiocyanate, etc.…”
Section: Photoluminescencementioning
confidence: 99%
“…388–391,393 The solid-phase fluorometric assay could provide a wide LDR 1.3–6500 μM with a LOD of 1.3 μM. 386 The ultra-sensitive Cr( iii )-displacement fluorometric assay with fluorescein sodium dye anchored TpPa-1 could provide a wide LDR of 10 nM–10 mM (although in logarithmic scale) with sufficiently low LOD (7.08 nM) without interference from l -proline and urea. 392 However, the fluorescent CdTe quantum dots modified with Sambucus nigra bark lectin could provide lowest LOD (2.1 nM; converted from 0.67 ng mL −1 ) for fluorometric assay of Sia with a moderately wide LDR 3.88 nM–2.2 μM (converted from 12–680 ng mL −1 ) in linear scale without interference in commercial egg products.…”
Section: Analytical Approaches To the Assay Of Sia In Biological And ...mentioning
confidence: 99%